SOSIALISASI DAN EDUKASI BAHAYA PENGGUNAAN KOSMETIKA PEMUTIH KULIT DIKALANGAN REMAJA - Gultom, Evi Depiana (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Skin whitening products are one of the cosmetic products that contain active ingredients that can inhibit the formation of melanin or eliminate melanin that has already formed so gives the skin a whiter color. Limited knowledge about various cosmetic products bleach means that people do not know the negative impacts that can arise if they are not careful. Mercury, hydroquinone and retinoic acid are some of the active substances that are often misused by illegal cosmetic manufacturers. This activity was carried out with the aim of providing knowledge and skills to the community, especially students of Al Washliyah 3 Medan Private Vocational School. This activity is carried out using the counseling method and questions and answers about the material the dangers of using whitening cosmetics containing mercury and hydroquinone are continued with training to check cosmetic registration numbers at BPOM using an Android cellphone. From that activity carried out, it turns out that there are still many patients who do not know the dangers of using mercury, hydroquinone and retinoic acid in whitening cream and don't know how to check the registration number. cosmetics on the market. From this community service activity, it is hoped that students will know more about the dangers of mercury, hydroquinone and retinoic acid and can check directly on ordinary cosmetic products used everyday.